Ayurvedic Insight into Tonsillitis (Tundikeri) (AYUSHDHARA, 2025)
Tuṇḍikerī is an Ayurvedic condition classified under Mukha Roga and is described as a swelling at the base of the Hānusandhi (temporomandibular joint), resembling the Vanakarpaṣā phala cotton fruit). Based on its signs and symptoms, Tuṇḍikerī corresponds closely to tonsillitis i.e., the inflammation of the tonsils, which are paired, oval lymphoid tissues at the throat’s back. Typical features include swollen tonsils, Galāśūla (sore throat), Jvara (fever), Karṇaśūla (ear pain), Galoparodha (difficulty swallowing), and enlarged, tender lymph nodes in the neck region. Material and Methods: A 25-year-old male patient presenting with clinical features resembling Tundikeri (tonsillitis) was treated using Ayurvedic oral medications along with Pratisarana and Kawal. The patient's condition was assessed using Brodsky grading and other symptom-specific subjective parameters following a 45-day therapeutic regimen. Follow-up evaluations were conducted both during and after the treatment period to monitor progress and outcomes. Result: The subject showed marked improvement as depicted in the photographs taken before and after treatment. Discussion: While allopathic medicine may offer symptomatic relief for tonsillitis, it often falls short in ensuring complete recovery and preventing recurrence. In contrast, Ayurveda, as outlined in classical Samhitas, provides a comprehensive approach that includes both internal medications and external therapies such as Pratisarana and Kawal. This article highlights the effectiveness of these Ayurvedic treatment modalities in managing Tundikeri, demonstrating their potential for more sustainable and holistic outcomes. Conclusion: By adopting the holistic approach with external treatment modality an attempt is made to bring about satisfactory results.